Estudo do biopolímero extraído da colocasia esculenta para aplicação em formulações cosméticas - Martins, Vaniele Bugoni (2019)
Colocasia Esculenta has high levels of starch, protein, carbohydrates and mucilage. Mucilage has a high content of carbohydrates and proteins that combine to form the macromolecule AGP-glycoprotein arabinogalactan, and can be applied in several areas, such as food, pharmaceutical, chemical, cosmetic, among others. Therefore, the research aimed to extract and characterized by various analytical techniques mucilage of Colocasia Esculenta rose variety, also known as rose yam, or yam of pig. To study the potential thickener, stabilizing and emulsifying the mucilage and applying it in a cosmetic formulation in order to compare it to the commercial biopolymer Gum Xanthan, carrying out the stability study and sensorial analysis of the samples. The characterization analyzes by XRD showed that the mucilage of Colocassia Esculenta has standard characteristics characteristic of natural semicrystalline polymers. Slim structure, and good thermal stability, remaining stable up to temperatures of 225 ° C. In its composition, it has groupings of proteins and carbohydrates, which may be linked to the presence of AGP, interesting characteristics for several applications as potential thickener, emulsifier and stabilizer emulsions, confirmed by good capacity and emulsifying activity and emulsion stability. When mucilage (MC) was applied in cosmetic formulations, the stability study showed that the pH and density of the samples remained stable with values close to the standard sample prepared with Xanthan gum. For the viscosity, the samples prepared with the mucilage remained stable over time while with Xanthan gum showed instability. All samples presented a rheological characteristic of pseudoplasticity with flow behavior indexes lower than 1, a desirable characteristic for cosmetics, as it improves their applicability. At high concentrations, the MC favored the destabilization of the samples, when subjected to mechanical stress, and that together with other emulsifiers and commercial stabilizers, can interfere in the stability of the emulsions. By sensory analysis, samples containing low concentrations of mucilage have been described by evaluators as topical creams easy to spread, intermediate concentrations leave residues on the skin, and high concentrations are more viscous and stickier, as well as being well absorbed and leaving the skin fresh. Since the samples containing more MC were preferred by the evaluators. Regarding the use of natural ingredients and cosmetics by evaluators, the greater the frequency of use of cosmetic creams, the more knowledge and information related to the products the consumer is looking for, and the more worried about the reactions they can cause on the skin, thus favoring studies to the replacement and application of natural ingredients or derivatives for various cosmetic applications.